Rat lung transplantation model: modifications of the cuff technique - Tian, Dong (Ann Transl Med, 2020)
BACKGROUND: Although the cuff technique in rat lung transplantation (LTx) has a long history, it remains technically challenging. We have developed key tricks and modifications in the devices and the cuff technique that optimize the rat LTx model to achieve successful operations during a short learning period. METHODS: Altogether, 180 consecutive rats underwent orthotopic left LTx performed by a single surgeon using our modified devices and procedures. Allogeneic and syngeneic transplantation were performed using Lewis rats as recipients and Brown Norway and Lewis rats as donors. Allogeneic recipients were treated with cyclosporine during the first week. Recipients were sacrificed at various time points after ≥2 weeks. RESULTS: A special cuff-preparation plate was created using a petri dish and two foam blocks. This modified plate stabilizes the preparation and prevents donor lung compression. A “┴”-shaped incision was carved into the front wall of the pulmonary artery (PA) using micro-scissors. “V”-shaped incisions were made from the inferior-to-superior branches of the pulmonary vein (PV) and bronchus. A “pendulum model” was applied at implantation to make the hilar anastomosis tension-free and technically easier to perform. There were no intraoperative complications. Ten rats (5.6%) experienced partial or full pulmonary atelectasis. Five deaths (2.8%) due to pleural effusion occurred during the follow-up period. The operative times for heart-lung block retrieval, cuff preparation, cold ischemia, warm ischemia, and total procedure time were 8.4±0.8, 11.6±1.5, 25.1±2.2, 8.1±1.2, and 46.7±2.8 min, respectively. CONCLUSIONS: The key tricks and improvements we made in the cuff technique for rat LTx provided the advantages of expeditiousness, a low complication rate, and a high success rate.